Croatian adaptation of the revised Reading the Mind in the Eyes Test (RMET) - Kotrla Topić, Marina (Array, 2019)
The aim of this research was to translate and adapt the revised version of the "Reading the mind in the eyes test" (Baron-Cohen et al., 2001) to the Croatian language, and to provide preliminary data on its reliability, factor structure and convergent validity in a healthy population of Croatian students. After translation and adaptation, the Croatian version of the RMET was administered to 146 undergraduate and graduate students (84 female and 62 male participants). Together with the RMET, we administered the Emotional Empathy Scale (Raboteg-Šarić, 1993). Results show low internal consistency reliability of the Croatian adaptation of the RMET and adequate reliability measured with maximal reliability H coefficient. Confirmatory factor analysis marginally supports the unidimensional model. Convergent validity was marginally confirmed by a significant positive correlation between REMT and empathy. Additionally, we created a short version of the RMET, showing adequate fit indices, but containing only seven items. Internal consistency reliability and composite reliability for this scale were satisfactory. We propose further investigation of psychometric properties of the Croatian adaptation of the RMET with research in general, more representative population. We also propose investigating test-retest reliability, as well as discriminant validity of the test.